2021
DOI: 10.13080/z-a.2021.108.019
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of mycotoxins and their relation to nutrient composition of maize and grass silage

Abstract: In this study, samples of maize and grass silage were collected from various farms of Lithuania and were analysed for mycotoxins: aflatoxin B 1 (AFB 1 ), deoxynivalenol (DON), T-2 toxin (T-2) and zearalenone (ZEA), over the 2017-2019 period. Silage nutrient composition, including content of dry matter, crude protein, crude fibre, starch (for maize), and acidity (pH) were investigated, and fermentation degree was computed. All samples contained at least one mycotoxin, 85% of samples were co-contaminated with al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
(24 reference statements)
1
4
0
Order By: Relevance
“…Mycotoxin contamination is highly dependent on weather conditions and, therefore, can change both during the vegetation season and throughout the year [16,48,49]. This was partially the case in our study, where significant differences in DON, AFB1, and T-2 were observed between 2019 and 2020, as shown in Table 4 (p < 0.05).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Mycotoxin contamination is highly dependent on weather conditions and, therefore, can change both during the vegetation season and throughout the year [16,48,49]. This was partially the case in our study, where significant differences in DON, AFB1, and T-2 were observed between 2019 and 2020, as shown in Table 4 (p < 0.05).…”
Section: Discussionsupporting
confidence: 55%
“…In our study, there were no increased levels of DON, AFB1, or T-2 in the biomass when compared to the unfertilized control, which suggests that there was no increased contamination by fungal producers of these mycotoxins. Venslovas et al came to similar conclusions in grass silage [49]. Therefore, the risks of such contamination are not increased using digestate on permanent grasslands, but more research is needed on other agricultural crops.…”
Section: Discussionmentioning
confidence: 78%
“…Zachariasova et al [ 21 ], however, state that maize leaves and corncobs contain higher amounts of protein and polysaccharides than grass, therefore they provide suitable conditions for surviving and spreading of fungi and other microorganisms. Moreover, in the study of Venslovas et al [ 38 ], negative correlation between crude protein and crude fiber levels as well as ZEN concentration in silage samples was found. Higher percentage of protein-rich components occur in legumes species.…”
Section: Discussionmentioning
confidence: 96%
“…Presence of mycotoxins in key fodder crops such as maize as well as in small grain cereals and legumes e.g. pea and soy is well known [ 21 , 37 , 38 ]. Infection by toxicogenic fungi depends on many abiotic factors, such as weather conditions, nutrient deficiency or excess, and biotic factors, such as insect damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation